Small family business as regulation method of labor market - Mussayeva , G.I. (BUKETOV BUSINESS REVIEW, 2017)
Article examines the role of small entrepreneurship, including family business as the method of regulation of regional labor market, promoting the increase of population’s employment and decrease of unemployment level. Main directions of state support of small entrepreneurship are defined, factors are found, influencing the conditions and perspectives of development of regional labor market, one of them is small family business as the source of demand formation in labor market. It is small family business in Kazakhstan economics, which promotes the creation of new workplaces, and executes the number of the most important social and economical functions: provision of employment, formation of competitive environment, support of innovative activity, decrease of social tension. The level of development of small business directly determines the level of population welfare, the degree of national economy development in general.In connection with,the need to support the small business in Kazakhstan is accepted as one of priority problems of economic policy today.Author analyzed the situation in labor market, level of employment of rural population in sectors of small and medium entrepreneurship, problems of family business development, factors of its successful development, conditions for regeneration of family business in Kazakhstan and development of modern family business, which demonstrate the stability and efficiency in most regions of the world. According to the results of the study, exact recommendations are offered for future development of small family business.